Potencial empreendedor em indivíduos com transtorno do espectro autista: uma perspectiva para o desenvolvimento - Pozzer, Ranice Höehr Pedrazzi (2021)
This research has the objective of analyzing the behavior characteristics related to the entrepreneurial potential in individuals with Autism Spectrum Disorder (ASD), considering the influence of family members and their preparation for professional practice. ASD is a syndrome manifested by alterations in language development and social interaction. Individuals with ASD present stereotyped, repetitive and ritualized behaviors, as well as restricted interests and sensory alterations, with varying levels of severity, which justifies the use of the term autism spectrum. Although autism is characterized as a complex developmental disorder, defined from a behavioral point of view and characterized by difficulties in social interaction that may be manifested as isolation, inappropriate social behavior, among other symptoms (GADIA et al., 2004, p. 584), reports of autistic people who managed to overcome the disorder and, as far as possible, developed skills that allow them to live a productive life are not uncommon. Some of them, such as Temple Grandin, for example, use their differentiated manner of looking at reality as an instrument for transformation, which is in line with the definitions of entrepreneurship. Entrepreneurship, in the view of Santos et al. (2014), is intrinsically dependent on individual decisions and actions (even if external factors are decisive for the entrepreneurial action), thus justifying the choice for entrepreneurial potential as an element of the construct that is being adopted in this research. The entrepreneurial potential, which is related to individual characteristics, may never become an entrepreneurial intention, but it brings with it a set of behavioral attributes that can be developed, allowing the establishment of skills and capacities that are of interest to the job market. To answer the problem of this research, four studies was carried out involving the conceptualization of entrepreneurial potential related to individual development, the identification of entrepreneurial potential in individuals with ASD and in their family members – and how these potential influences the autistic person’s development – and the verification of the skills that the job market has observed in professionals with ASD who have been working. This study is based on the relationship family – autistic person – company, from the construct that involves entrepreneurial potential, cognition and autism spectrum disorder. With the first study, it was possible to identify a theoretical gap – Entrepreneurial Potential and entrepreneurial characteristics in neuroatypicals, being the construct an emerging topic if associated with education, education for work, development and knowledge. The second study showed that behavioral characteristics of autistic people find similarities in the behavioral characteristics related to Entrepreneurial Potential and that this can be used to promote professional inclusion. The third study showed that there are influences of characteristics of the Entrepreneurial Potential of parents in the development of their children, considering the overcoming of the diagnosis and resilience. And the fourth study pointed out that hiring autistic people can be geared to results and not just functionality. Thus, this thesis shows that the Entrepreneurial Potential can be a perspective for the development of the autistic person, aiming at insertion in the job market.